Penyidikan Terhadap Anak Pelaku Tindak Pidana Perundungan (Bullying) Di SDN 10 Durian Jantung Padang Pariaman (Studi Kasus: Lp/B/70/V/2024/Spkt/Polres Pariaman/Polda Sumbar) - Nurlinda Yenti; Ester Waruwu (Normative Jurnal Ilmiah Hukum, 2026)
An investigation is a series of actions by investigators, in accordance with the procedures stipulated in this Law, to seek and collect evidence and identify suspects.The problem formulation is: How is the investigation of children as perpetrators of bullying at SDN 10 Durian Jantung? What are the obstacles to the investigation of children as perpetrators of bullying at SDN 10 Durian Jantung? How are obstacles to the investigation of children as perpetrators of bullying at SDN 10 Durian Jantung? This research method uses a sociological legal approach with a descriptive nature. The types and sources of data use primary and secondary data. Primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques use document studies and interviews. Data processing uses editing and coding, and data analysis uses qualitative methods.The results of this study are: The reported party or child in conflict with the law (ABH) cannot be arrested, searched, detained, or questioned because they are still 10 years old. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System states that children who can be held criminally responsible are those aged 12 but under 18.Children under 12 years of age were returned to their parents.The investigation encountered obstacles, including the failure to find evidence, as the gasoline bottle caught fire. Efforts to overcome these obstacles included investigators incorporating the missing evidence into the search and shifting to gathering other evidence by interviewing witnesses, which was deemed more strategic and easier, to allow the investigation to continue.